The Role of the Regional Advisory and Supervisory Board Regarding the Responsibilities of Temporary Land Deed Making Officials in Storing Protocols - Ahmad Firdaus; Rosita Indrayti; Andika Putra Eskanugraha (Res Judicata Law Review, 2024)
PPAT is an important part of the land registration system in Indonesia which has the authority to make authentic deeds. The main task of PPAT is to make deeds stating that certain legal acts related to land ownership have been fulfilled which will be the basis for data on land transfer registration. In order to maintain quality and continue to carry out its duties carefully, guidance and supervision are needed for PPAT. Based on Article 1 of PMNA/KBPN 2/2018, the Minister authorizes MP2D to carry out guidance and supervision of PPAT in the form of conveying policies that have been determined by the Minister regarding the implementation of PPAT duties, socialization, dissemination, inspections to PPAT offices, and guidance on the implementation of PPAT duties and functions in accordance with the Code of Ethics. Guidance and supervision of PPAT as regulated in the ministerial regulation also applies to PPATS, Substitute PPAT, and Special PPAT. However, there are still many legal problems found, such as not reading or explaining the deed in front of the parties and witnesses, and especially related to the storage of PPAT protocols. The normative research method used in this study is the type of normative juridical legal research using 2 (two) legal approaches, namely the legislative approach and the conceptual approach. The Result is MP2D plays a role in supervising PPAT, especially PPATS in carrying out its duties to ensure that PPATS has carried out its duties and functions as mandated by the Head of the Land Office, to maintain and ensure that services continue to run in accordance with the provisions of laws and regulations, ensure that professional ethics are well maintained, minimize violations, provide understanding, improve discipline and service to PPATS, especially related to maintaining the PPATS protocol which is a state archive that must be maintained, cared for and stored properly and safely.